2021
DOI: 10.1016/j.yebeh.2021.107833
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the coronavirus disease (COVID-19) pandemic on outpatient epilepsy care: An analysis of physician practices in Germany

Abstract: Objective To gain insight into epilepsy care during coronavirus disease (COVID-19) pandemic, we analyzed prescription data of a large cohort of persons with epilepsy (PWE) during lockdown in Germany. Methods Information was obtained from the Disease Analyzer database, which collects anonymous demographic and medical data from practice computer systems of general practitioners (GP) and neurologists (NL) throughout Germany. We retrospectively compared prescription data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…These results were also observed for other chronic diseases with a care reduction for newly diagnosed persons (e.g. epilepsy), whereas adherence to treatment remained stable for patients who were already being treated 6 . A decrease in the dispensation of systemic anticancer therapy delivery was also observed during the first wave of the pandemic, with a global treatment reduction of 30% (from 20% for breast cancer to 43% for colorectal cancer) 7 .…”
Section: Figurementioning
confidence: 58%
“…These results were also observed for other chronic diseases with a care reduction for newly diagnosed persons (e.g. epilepsy), whereas adherence to treatment remained stable for patients who were already being treated 6 . A decrease in the dispensation of systemic anticancer therapy delivery was also observed during the first wave of the pandemic, with a global treatment reduction of 30% (from 20% for breast cancer to 43% for colorectal cancer) 7 .…”
Section: Figurementioning
confidence: 58%
“…Of these, eleven were excluded as the focus was on caregivers (n=2), epileptologists (n=1), focus on children (n=1), or had outcomes irrelevant to search (n=7). Lastly, six articles were eligible, of which one had a retrospective cohort design [22] , two had a prospective cohort design [23] [24] , one had a case-control study design [25] , and two a cross-sectional design [26] [27] , yielding a total sample of 54585 people with epilepsy. We identified four overarching aspects: change of ASM compliance, and as risk factors, follow-up, difficulties accessing ASM, and behavioural risk factors found to be associated with adherence.…”
Section: Resultsmentioning
confidence: 99%
“…In four studies, it was self reported, [24] [25] [26] [27] of which one used the modified Morisky scale was used [24] , one study provided no definitions [23] and one study used prescription data as a proxy for adherence during the lockdown. [22] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 In a recent international survey, most PWE (74.2%) reported satisfaction with either a phone or video consult with their neurologist as an alternative to in-person appointments. 4 Similarly, in a survey of PWE and their clinicians, tele-medicine was found to be both effective and satisfactory in the delivery of chronic outpatient care to PWE. 5 However, the suitability/appropriateness of telemedicine practice for newly diagnosed PWE has been questioned by some clinicians.…”
mentioning
confidence: 95%